Factors associated with nursing work climate deterioration as related to shift exchanges - Danelia Gómez-Torres; Karla Sofia Gómez-Alcántara; David Fuentes-García; Claudio Emilio León-González (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To uncover the factors that deteriorate the work environment during shift exchanges. Method: This is a qualitative, descriptive-analytical study using the phenomenological method, based on Elton Mayo's human relations theory. The setting was a second-level hospital. A total of thirty-two participants were included. The social actors included were general nurses, specialists, and service managers. Data collection was carried out using interviews and non-participant observation techniques, conducted in September-October 2021. Data analysis was performed in three stages: epoché, description, and horizontalization. The chromatic technique was used for analysis. Results: The main findings converge into three categories: workload, as it affects the quality of care; absenteeism, which increases handover time; and interpersonal relationships, which influence the handover process. Observations allowed for the creation of a shift exchange model represented by a flowchart and a patient reception instrument. Final considerations: Workload and interpersonal relationships directly influence the work environment.